MAKNA DAN FUNGSI EMOTIKON DALAM NOVEL (NEUKDAEEUI YUHOK I) KARYA GWIYONI: KAJIAN SEMIOTIKA PIERCE - , TRI ISTIYANI, Dr. Novi Siti Kussuji Indrastuti, M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Using semiotic method,this Graduating Paper entitled âMeanings and Functions of Emoticons in (Neukdaeeui Yuhok I), a novel by Gwiyoni: Peirce Semiotic Analysisâ contained analysis of meanings and functions of emoticons. The novel, (Neukdaeeui Yuhok I) used as material object because it applies emoticons on its writing. This graduating paper is essentially purposed to inform and as discourse on meanings and functions of emoticons in art literature. This emoticonâs meaning was analyzed with using Peirceâs Meaning-Triangle-Theory. It can be inferred from this research that (Neukdaeeui Yuhok I) novel has 33 types variation of emoticons. All of these 33 types of emoticons are classified based on its meaning. According to the classification, emoticons meaning in the (Nekdaeeui Yuhok I) novel can be divided into 12 types